PTH-096 Management of Hepatocellular Carcinoma (HCC) In A Tertiary HPB Centre- Lessons from The South East Coast-The Royal Surrey County Hospital (RSCH). (17th August 2016) - Kelly, C; Pericleous, M; Bagwan, I; Worthington, T; Gallagher, M; Tibbs, C; Dhillon, T; Karanjia, N; Ala, A
Abstract : Introduction: The UK is facing an epidemic of liver disease, with end stage liver disease and HCC increasingly reported. Biannual surveillance is recommended (BSG, EASL, AASLD) for cirrhotic patients to aid early HCC diagnosis. Resection and transplantation remain the treatment options with curative intent. Our tertiary HPB centre covers a population of 2.1 million in the South of England and has seen an increasing number of referrals to our regional HCC MDT. Here we present our experience on our cohort from 2010 current Methods: HCC patients were identified from MDT records as well as histology specimens, oncology and hepatology clinical records. Medical records including primary care were reviewed where necessary. Statistical analysis was performed using SPSS v21 Results: 113 patients were managed in our centre during the examined period. There was a 7 fold increase in the number of patients receiving treatment in the last 12 months (n = 45). The median age at presentation was 70 years. The ratio of female: male was 1:3.2. HCC was established histologically in 36% (biopsy n = 20 and resection n = 21), the rest on tumour markers and radiology. 57% had cirrhosis. In those with liver disease the commonest diagnoses were viral hepatitis, ALD & NASH. The mean overall survival (OS) was 12 months. Overall and disease free survival with resection was 34 and 30 months respectively which is significantly higher than other groups (p < 0.001). The median OS comparing cirrhotics and non cirrhotics (10 months v 13 months) was not statistically significant. No significant survival difference was seen with gender or age (cut off 70 yrs). Analysis of resected patients showed mean survival for patients with 1 tumour was 42.5 months and more than 1 tumour 22.5 months Conclusion: Our experience demonstrates a significant number of HCC resections in livers with normal histological sampling and non-cirrhotic livers, agreeing with literature describing HCC rates of up to 40% in specific non-cirrhotic populations. The success of our resections is complemented by the recent availability of loco regional therapy (SIRT, TACE & RFA) in our unit. Patients with compensated cirrhosis and advancing age should still be considered for resection given its curative intent and long-term outcomes. Our data shows consideration should be given to widening HCC surveillance guidelines to capture these high-risk groups with early or no liver disease Reference: 1 Williams R, Aspinall R, Bellis M, et al . Addressing liver disease in the UK: a blueprint for attaining excellence in health care and reducing premature mortality from lifestyle issues of excess consumption of alcohol, obesity, and viral hepatitis. Lancet 2014;384 :1953–97. Disclosure of Interest: None Declared